A Tolerability and Pharmacokinetic Study of Adjuvant Erlotinib and Capecitabine with Concurrent Radiation in Resected Pancreatic Cancer - Ma, Wen Wee (Neoplasia Press Inc., 2010)
BACKGROUND: Erlotinib is approved for the treatment of advanced pancreas cancer. We conducted a prospective trial to determine the safety profile and recommended phase 2 dose of erlotinib and capecitabine given concurrently with intensity-modulated radiation therapy (IMRT) in resected pancreatic cancer patients. The pharmacokinetic profile of this combination was also evaluated. METHODS: Patients with resected pancreatic adenocarcinoma received erlotinib and capecitabine concurrently with IMRT delivered at 1.8 Gy daily in 28 fractions (total = 50.4 Gy). The starting dose level (DL 1) was erlotinib 150mgdaily and capecitabine 800 mg/m(2) twice daily without interruption. The next lower dose level (DL -1) was erlotinib 100 mg daily and capecitabine 800 mg/m(2) twice daily (Monday to Friday). Plasma samples were obtained for pharmacokinetic analysis. RESULTS: Thirteen patients were enrolled in total. At DL 1, six of the seven treated patients were evaluable for toxicities. Four completed planned treatment, but all required treatment interruption or dose reduction. The dose-limiting toxicities were neutropenia, diarrhea, and rash. Six patients were subsequently enrolled to and completed planned treatment in DL-1. Themost common toxicities were fatigue, elevated liver enzymes, and anorexia. The pharmacokinetic parameters of erlotinib and OSI-420 were not significantly different in the presence or absence of capecitabine and were consistent with historical controls. CONCLUSIONS: When administered concurrently with IMRT, erlotinib 100 mg daily and capecitabine 800 mg/m(2) twice daily (Monday to Friday) can be administered safely in resected pancreas cancer patients, and is the recommended regimen for efficacy studies using this regimen.